2001
DOI: 10.1007/s002460010180
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Study of Postcoronary Arteritis in Adolescents and Young Adults: With Reference to the Relationship Between Sequelae of Kawasaki Disease and Atherosclerosis

Abstract: To clarify whether the cardiac sequelae of Kawasaki disease (KD), postcoronary arteritis lesions can become a risk factor for atherosclerosis of the coronary arteries, six autopsy cases of patients older than 15 years of age with coronary arterial lesions caused by arteritis in childhood were examined histologically. Twenty-four arteries were inspected: 10 had no evidence of aneurysm formation, 7 arteries manifested simple dilatation of the lumen, and in 7 arteries there were aneurysms with recanalization. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 8 publications
4
97
0
Order By: Relevance
“…[4][5][6] The mechanism responsible for this finding is unclear, however, differences in tissue composition of vessel walls might play a role. Thickened intima in KD coronary sequelae is generally composed of fibrous tissue with lower cell density, inconsistent with adult atherosclerotic plaque, 1) implying lower proliferative properties of intima in KD sequelae in response to PCI-related vessel injury. In the present case, however, during the first PCI, OFDI delineated fibrofatty plaque at the culprit site, indicating the presence of early atherosclerotic change in KD sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] The mechanism responsible for this finding is unclear, however, differences in tissue composition of vessel walls might play a role. Thickened intima in KD coronary sequelae is generally composed of fibrous tissue with lower cell density, inconsistent with adult atherosclerotic plaque, 1) implying lower proliferative properties of intima in KD sequelae in response to PCI-related vessel injury. In the present case, however, during the first PCI, OFDI delineated fibrofatty plaque at the culprit site, indicating the presence of early atherosclerotic change in KD sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Since these stiff calcified lesions have risk of stent underexpansion and neo-aneurysmal formation ascribed to high-pressure balloon inflation, rotational atherectomy with/without additional low-pressure balloon dilation alone has been a mainstay of interventional treatment for stenosis due to the coronary sequelae of KD. [4][5][6] In contrast, drug-coated balloons (DCB) now play a central role in the treatment of in-stent restenosis through their inhibition of neointimal hyperplasia, despite the lack of evidence for de novo coronary artery disease.…”
mentioning
confidence: 99%
“…Likewise, no atheromatous plaques were found in seemingly normal coronary arteries distal to aneurysmsin 10 autopsied adults KD patients (Burns et al, 1996). On the contrary, Takahashi et al reported that 3 patients who were 15, 20, and 39 years of age had new intimal thickening, including atheroma-like bright areas and foamy macrophages in CALs (Takahashi et al, 2001). Also, Negoro et al showed that a substantial lipid core with cholesterol crystals and macrophages was found in an atherectomy specimen from a stenotic lesion in a 32-year-old man who presented with acute coronary syndrome (Negoro et al, 2003).…”
Section: Pathological Featuresmentioning
confidence: 96%
“…Even in coronary arteries in which there is no aneurysm formation in the acute phase, mild intimal thickening may be seen in some patients (Takahashi et al,2001). Therefore, there is some debate about the possibility that a history of KD might be a risk factor in the progression of atherosclerosis.…”
Section: Coronary Artery With No Aneurysm Formationmentioning
confidence: 99%
“…Recanalized lumens may become stenotic due to the proliferation of cellular fibrous tissues, and active remodeling is present at the site of aneurysms even during the remote phase. 39,42 c. Coronary Arteries Without Aneurysm Formation Autopsy of patients with a history of Kawasaki disease who died from causes other than the disease has revealed diverse findings in arteries including clear scars of healed arteritis 43 and no scars. 44 There is no medical consensus about long-term prognosis of coronary artery lesions due to Kawasaki disease.…”
Section: B Arteries With Remaining Aneurysmsmentioning
confidence: 99%